Respuesta :
hello :
x+y = 2.....(1)
y= (-1/4)x²+3...(2)
by (1) : y = -x+2
subsct in (2) : -x +2 =( -1/4)x²+3
-4x+8 = -x² +12
x²-4x - 4 =0
(x² -4x +4) -4 -4 =0
(x-2)² = 8 =(2√2)²
x-2 = 2√2 or x-2 = - 2√2
x= 2+ 2√2 or x= 2- 2√2
if : x= 2+ 2√2 .....y = -( 2+ 2√2 )+2 = - 2√2
if : x= 2- 2√2 .....y = -( 2- 2√2 )+2 = 2√2
two solutione : (2+ 2√2 , - 2√2 ) , (2- 2√2 , 2√2 )
x+y = 2.....(1)
y= (-1/4)x²+3...(2)
by (1) : y = -x+2
subsct in (2) : -x +2 =( -1/4)x²+3
-4x+8 = -x² +12
x²-4x - 4 =0
(x² -4x +4) -4 -4 =0
(x-2)² = 8 =(2√2)²
x-2 = 2√2 or x-2 = - 2√2
x= 2+ 2√2 or x= 2- 2√2
if : x= 2+ 2√2 .....y = -( 2+ 2√2 )+2 = - 2√2
if : x= 2- 2√2 .....y = -( 2- 2√2 )+2 = 2√2
two solutione : (2+ 2√2 , - 2√2 ) , (2- 2√2 , 2√2 )
Answer with explanation:
We are given a system of equation as:
[tex]x+y=2-----------(1)\ ;\ y=\dfrac{-1}{4}x^2+3------------(2)[/tex]
- We solve the system by the method of substitution.
i.e. we substitute the value of y from equation (2) into equation (1) and find the value of x.
and finally putting the value of x back to equation (2) and get the value of y.
- Hence, we solve the equation as follows:
We put the value of y from equation (2) into equation (1) to get:
[tex]x-\dfrac{1}{4}x^2+3=2\\\\\\i.e.\\\\x-\dfrac{1}{4}x^2=2-3\\\\i.e.\\\\x-\dfrac{1}{4}x^2=-1\\\\\\i.e.\\\\4x-x^2=-4\\\\i.e.\\\\x^2-4x-4=0[/tex]
The solution of the quadratic equation:
[tex]ax^2+bx+c=0[/tex]
is given by:
[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
Here,
[tex]a=1,\ b=-4\ and\ c=-4[/tex]
Hence, the solution is:
[tex]x=\dfrac{4\pm \sqrt{(-4)^2-4\times (-4)\times 1}}{2\times 1}\\\\i.e.\\\\\\x=\dfrac{4\pm \sqrt{32}}{2}\\\\i.e.\\\\x=\dfrac{4\pm 4\sqrt{2}}{2}\\\\i.e.\\\\x=2\pm 2\sqrt{2}[/tex]
Case--1:
Now,
when [tex]x=2+2\sqrt{2}[/tex]
Then
[tex]y=\dfrac{-1}{4}(2+2\sqrt{2})^2+3\\\\i.e.\\\\y=\dfrac{-1}{4}[4+8+8\sqrt{2}]+3\\\\i.e.\\\\y=\dfrac{-1}{4}[12+8\sqrt{2}]+3\\\\i.e.\\\\y=-3-2\sqrt{2}+3\\\\i.e.\\\\y=-2\sqrt{2}[/tex]
Case--2:
Now,
when [tex]x=2-2\sqrt{2}[/tex]
[tex]y=\dfrac{-1}{4}(2-2\sqrt{2})^2+3\\\\i.e.\\\\y=\dfrac{-1}{4}[4+8-8\sqrt{2}]+3\\\\i.e.\\\\y=\dfrac{-1}{4}[12-8\sqrt{2}]+3\\\\i.e.\\\\y=-3+2\sqrt{2}+3\\\\i.e.\\\\y=2\sqrt{2}[/tex]
Hence, the solution to the system are:
[tex](2+2\sqrt{2},-2\sqrt{2})\ and\ (2-2\sqrt{2},2\sqrt{2})[/tex]